PERAN KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT AJS SIDOARO - Muhammad Khoirul Nur Rokhim; Endang Iryanti (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine and analyze the effect of compensation and work discipline on employee performance at PT Adikara Jaya Sentosa. The type of research used is quantitative, with a population consisting of all 50 employees. Due to the relatively small population size, a saturated sampling technique was employed, in which the entire population was used as the sample. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares through SmartPLS software. A series of tests were conducted, including validity and reliability tests, as well as the R-Square test. The results of the structural model testing consistently proved that compensation and work discipline partially have a positive and significant effect on the employee performance of PT Adikara Jaya Sentosa.